2018
DOI: 10.3390/ijms19123947
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Bradyrhizobium diazoefficiens Bacteroids Reveals a Post-Symbiotic, Hemibiotrophic-Like Lifestyle of the Bacteria within Senescing Soybean Nodules

Abstract: The form and physiology of Bradyrhizobium diazoefficiens after the decline of symbiotic nitrogen fixation has been characterized. Proteomic analyses showed that post-symbiotic B. diazoefficiens underwent metabolic remodeling as well-defined groups of proteins declined, increased or remained unchanged from 56 to 119 days after planting, suggesting a transition to a hemibiotrophic-like lifestyle. Enzymatic analysis showed distinct patterns in both the cytoplasm and the periplasm. Similar to the bacteroid, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…They also synthesize appendages [13], and the protein [10] and RNA levels (Figure 1C) remain constant. Strodtman et al have shown that post-symbiotic bacteria remain metabolically active up to 119 days after planting [24]. The retention of transcriptional, translational [24], and metabolic [24] activities of the bacteria as the plant cells dies is behavior reminiscent of a hemibiotroph [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also synthesize appendages [13], and the protein [10] and RNA levels (Figure 1C) remain constant. Strodtman et al have shown that post-symbiotic bacteria remain metabolically active up to 119 days after planting [24]. The retention of transcriptional, translational [24], and metabolic [24] activities of the bacteria as the plant cells dies is behavior reminiscent of a hemibiotroph [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Strodtman et al have shown that post-symbiotic bacteria remain metabolically active up to 119 days after planting [24]. The retention of transcriptional, translational [24], and metabolic [24] activities of the bacteria as the plant cells dies is behavior reminiscent of a hemibiotroph [25,26]. A hemibiotroph is an organism that is saprophytic or parasitic in living tissue while the plant is alive and upon plant death consumes the dead tissue [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The content of PHB in bacteroids is dependent on the relative rates of synthesis and degradation during active nitrogen fixation (Lodwig & Poole, 2003). High accumulation of PHB in bacteroids is a feature of senescing nodules in different legumes (Hernández‐López et al., 2018; Li et al., 2015; Strodtman et al., 2018), which could be due to a variety of causes, including a shift in the redox state of the cell, shifts in the nitrogen–carbon balance, or disruption in the ability to degrade and utilize PHB. Lastly, the higher number of nodules produced in gmuox1 roots (Figure 1c) is consistent with previous reports on Fix − mutants in legumes (Bourcy et al., 2013; Wang et al., 2016; Xi et al., 2013), which was suggested to compensate for the fixation deficiency in the mutant roots.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, their presence can reduce the proliferation and multiplication of free-living rhizobia in the soil, delaying or inhibiting nodule formation [186][187][188][189]. Nitrogen fertilizer application also leads to premature nodule senescence and feedback inhibition of nitrogenase activity [190][191][192][193][194][195][196]. The inhibitory effects of nitrogen fertilizers on nodulation are likely plant-mediated, and different strains of rhizobia exhibit varying degrees of tolerance to these effects [197,198].…”
Section: Effect Of N Fertilizer On Root-hair Curling Infection Thread...mentioning
confidence: 99%